Pengaruh Budaya Sekolah terhadap Prestasi Kerja Guru Melalui Semangat Kerja : Studi di SDN Tamberu Laok 1 Sokobanah Kabupaten Sampang - Woro Utari; Moh. Nur Efendi; Chamariyah Chamariyah (Universitas 45 Surabaya, 2025)
This type of research uses explanatory research, the research approach uses a quantitative approach. The research sample was 42 respondents. The aim of this research is 1) To examine and analyze the significant influence of school culture on the work performance of teachers at SDN Tamberu Laok 1 Sokobanah, Sampang Regency. 2) To test and analyze the significant influence of school culture on the work spirit of teachers at SDN Tamberu Laok 1 Sokobanah, Sampang Regency. 3) To test and analyze the significant influence of work enthusiasm on the work performance of teachers at SDN Tamberu Laok 1 Sokobanah, Sampang Regency 4) To test and analyze the significant indirect influence of school culture on the work performance of teachers at SDN Tamberu Laok 1 Sokobanah, Sampang Regency, which is mediated by work enthusiasm. The research results show that: 1) School culture has a positive and insignificant effect on the work performance of teachers at SDN Tamberu Laok 1 Sokobanah, Sampang Regency with an original sample value of 0.192. 2) School culture has a significant positive effect on work morale at SDN Tamberu Laok 1 Sokobanah, Sampang Regency with an original sample value of 0.623.3) Work enthusiasm has a significant positive effect on the work performance of teachers at SDN Tamberu Laok 1 Sokobanah, Sampang Regency with an original sample value of 0.682. 4) Indirectly, school culture has a significant effect on the work performance of teachers at SDN Tamberu Laok 1 Sokobanah, Sampang Regency, which is mediated by work enthusiasm with an original sample value of 0.425.